2010
DOI: 10.1007/s00421-010-1529-0
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanical loading protocols influence serum cartilage oligomeric matrix protein levels in young healthy humans

Abstract: The purpose of the study was to investigate whether a relationship between the loading mode of physical activity and serum cartilage oligomeric matrix protein (COMP) concentration exists and whether the lymphatic system contributes to COMP release into the serum. Serum COMP levels were determined in healthy male subjects before, after and at 18 further time points within 7 h at four separate experimental days with four different loading interventions. The loading intervention included high impact running exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
87
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(101 citation statements)
references
References 31 publications
(63 reference statements)
11
87
3
Order By: Relevance
“…Immediately and 24 hours after the marathon race, more than half of our participants had values above 15 U/L previously related to a high risk of aggressive joint destruction (Andersson et al, 2013). Increases in COMP in this study were greater than those reported for shorter running exercises (Denning et al, 2014;Kersting et al, 2005;Niehoff et al, 2010;Niehoff et al, 2011) and comparable to observed changes after marathon races (Kim et al, 2009;Neidhart et al, 2000). In contrast to a previous study (Neidhart et al, 2000), COMP concentrations did not return to baseline within 24 hours after the marathon in all runners.…”
Section: Cartilage Biomarkerscontrasting
confidence: 54%
See 1 more Smart Citation
“…Immediately and 24 hours after the marathon race, more than half of our participants had values above 15 U/L previously related to a high risk of aggressive joint destruction (Andersson et al, 2013). Increases in COMP in this study were greater than those reported for shorter running exercises (Denning et al, 2014;Kersting et al, 2005;Niehoff et al, 2010;Niehoff et al, 2011) and comparable to observed changes after marathon races (Kim et al, 2009;Neidhart et al, 2000). In contrast to a previous study (Neidhart et al, 2000), COMP concentrations did not return to baseline within 24 hours after the marathon in all runners.…”
Section: Cartilage Biomarkerscontrasting
confidence: 54%
“…For instance, serum concentrations of cartilage oligomeric matrix protein (COMP) increase after exercise bouts of walking (Mündermann, Dyrby, Andriacchi, & King, 2005;Mündermann, King, Smith, & Andriacchi, 2009;Pruksakorn et al, 2013), running (Kersting, Stubendorff, Schmidt, & Bruggemann, 2005;Niehoff et al, 2010;Niehoff et al, 2011) and marathon running (Neidhart et al, 2000) but not after deep knee bends (Niehoff et al, 2010). Hence, load-induced changes in COMP appear to be sensitive to load magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…7, 9, 13, 16, 30, 35, 36 Serum COMP levels are elevated after intense exercise, 23, 33 and are elevated in subjects who participated in less strenuous forms of physical activity. 31, 32, 34 This indicates that exercise stresses the articular cartilage. However, the balance of cartilage turnover caused by exercise and that which may cause long term ramifications is unknown.…”
Section: Introductionmentioning
confidence: 98%
“…COMP is an established biomarker for joint degeneration and cartilage thinning [16], [17], and its serum level increases with mechanical loading [18], [19], [20]. Erhart-Hledik et al [16], for example, showed that a short-term change in serum COMP concentration induced by a mechanical stimulus is associated with long-term degenerative morphological changes in cartilage at the tibiofemoral joint.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine potential changes in cartilage response in the elderly due to the motor task reorganization, serum levels of cartilage oligomeric matrix protein (COMP) as a biomarker of cartilage metabolism were analyzed after a controlled incline walking exercise on the treadmill. COMP is currently being studied as a serum marker for cartilage degeneration in OA and knee joint disease [16], [17], and its serum level increases with cyclic mechanical loading [18], [19], [20]. Therefore, we additionally aimed to test the hypothesis that the consequences of the lower ambulatory knee joint loading in the elderly after the improvement of the TS and QF MTU capacities would influence cartilage metabolism by decreasing the serum COMP concentration after the cyclic loading exercise.…”
Section: Introductionmentioning
confidence: 99%